Draft Annual Plan 1993-94 Andhra Pradesh Volume-II (Sectoral Programmes) 10. General Economic Services and General Services - Planning Commission (Planning Commission, 1992)
An outlay of Rs.345.00 lakhs is proposed for the year 1993-94 under “Secretariat Economic Services” of which Rs.245.00 lakhs is towards normal plan schemes and Rs. 100.00 lakhs is under the Cyclone Emergency Reconstruction Project for which the Planning Department is the nodal Department to coordinate the works taken up under the various programmes to undertake works meant for reconstruction of the cyclone affected areas in the State.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh